2021
DOI: 10.2147/nss.s328218
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Objectively Measured Gait Speed and Subjective Sleep Quality in First-Year University Students, According to Gender

Abstract: Purpose To examine the associations between gait speed and sleep quality in first-year university students, according to gender. Methods In this cross-sectional study, we recruited 193 first-year university students [mean age±standard deviation (SD): 19.6±1.1 years; mean height: 178.0±10.5 cm; mean weight: 74.0±11.0 kg; 26.9% women). Sleep quality was assessed using the Pittsburgh Sleep Quality questionnaire, with a lower score indicating “better” sleep quality. Gait sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The present study showed that Chinese adults aged 50 years or over with poor sleep quality or longer sleep duration had significantly slower normal walking speed. These findings are consistent with previously published work ( Kasović et al, 2021 ). However, conflicting results on sleep quality and normal walking speed have been reported.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that Chinese adults aged 50 years or over with poor sleep quality or longer sleep duration had significantly slower normal walking speed. These findings are consistent with previously published work ( Kasović et al, 2021 ). However, conflicting results on sleep quality and normal walking speed have been reported.…”
Section: Discussionsupporting
confidence: 94%
“…An early study of Agmon et al (2016) indicated that older adults with poor sleep quality had a worse performance under dual tasks, implying the compromise of gait ability. Furthermore, Kasović et al (2021) reported that participants who walked at a fast speed had significantly good sleep quality in emerging adults. Of note, Nakakubo et al (2018) reported that excessive daytime sleepiness was associated with slower walking speed in Japanese younger and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study reported that moderate-to-high levels of physical exercise positively affect executive functions in middle-aged and older individuals [ 27 ]. A study in young adults suggested that good sleep quality was associated with higher gait speed in single-task conditions, but did not investigate during dual-task conditions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggest that the oxyhemoglobin was higher after a whole night’s sleep than at the beginning of the night [ 25 ]. Others reported that sleep plays an important role in the processes of learning and memory [ 26 ], that physical activity benefits the executive function [ 27 ] and gait speed [ 28 ], and that sedentarism [ 29 ], poor sleep quality [ 30 ], and more than 8 h of sleep duration [ 31 ] can be associated with lower gait speed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the United Arab Emirates (UAE) showed that young adults in medical colleges have shorter sleep durations than the recommended sleep guidelines, with an average of five hours and twenty-four minutes [8]. Additionally, the literature reports that 40% of young adults suffer from poor sleep quality worldwide [9].…”
Section: Introductionmentioning
confidence: 99%